Efektivitas Rebus Daun Sirih Merah dan Konsumsi Telur Ayam Rebus terhadap Luka Perineum pada Ibu Postpartum di PMB S Kabupaten Pandeglang Tahun 2024 - Aisah, Siti; Septa Rini , Ageng; Wulandari , Ratna (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Poor care of perineal wounds can cause infection which will slow down the healing process of perineal wounds. Efforts to prevent perineal wound infections can be provided with pharmacological therapy and non-pharmacological therapy. To provide midwifery care and determine the effectiveness of boiling red betel leaves and consuming boiled chicken eggs on perineal wounds in postpartum mothers. The research used is descriptive qualitative research. The target of the activity was 2 postpartum mothers who had perineal wounds who were given intervention 1 by giving boiled red betel leaves, and intervention 2 by giving boiled chicken eggs for 5 days. From the research results, it was found that postpartum mothers who experienced perineal wounds before and after being given intervention experienced accelerated healing of perineal wounds on the 4th day. There is an effect of boiled red betel leaves and boiled chicken eggs on accelerating the healing of perineal wounds in postpartum mothers. For postpartum mothers, consume boiled chicken eggs and red betel leaves to speed up the healing of perineal wounds.